2019
DOI: 10.1371/journal.pone.0225229
|View full text |Cite
|
Sign up to set email alerts
|

Performance of patient acuity rating by rapid response team nurses for predicting short-term prognosis

Abstract: BackgroundAlthough scoring and machine learning methods have been developed to predict patient deterioration, bedside assessment by nurses should not be overlooked. This study aimed to evaluate the performance of subjective bedside assessment of the patient by the rapid response team (RRT) nurses in predicting short-term patient deterioration.MethodsPatients noticed by RRT nurses based on the vital sign instability, abnormal laboratory results, and direct contact via phone between November 1, 2016, and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Nevertheless, they referred to criteria such as the Braden Scale to determine the risk of pressure ulcers and the Morse Fall Risk Assessment to predict certain conditions. Kim et al (39) point out in their study that although the warning scores of these criteria may be useful in identifying at-risk patients, direct examinations and ongoing surveillance by health care providers should be emphasized (39).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they referred to criteria such as the Braden Scale to determine the risk of pressure ulcers and the Morse Fall Risk Assessment to predict certain conditions. Kim et al (39) point out in their study that although the warning scores of these criteria may be useful in identifying at-risk patients, direct examinations and ongoing surveillance by health care providers should be emphasized (39).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the primary responder needs to determine whether the alarm is clinically important and requires immediate escalation to a higher level of management, or a false alarm. In our hospital, we studied the effectiveness of subjective assessment (patient acuity rating scale) of the triggered patient by experienced RRT nurses and confirmed that the subjective assessment scale of RRT nurses was superior to single parameter triggering or multi-parameter EWS in predicting the patient’s short term prognosis [ 31 , 32 ]. This result shows that an experienced and well-trained primary responder is crucial to an RRT.…”
Section: Key Strategies For the Efferent Limb: Qualified Primary Responders And Dedicated Physiciansmentioning
confidence: 93%
“…( 7 ) Recent studies have shown high variability in the accuracy of this score, which has led to uncertainty regarding its use. ( 2 , 4 , 9 , 10 ) Its role in the inter- or intrahospital transfer of patients is even more undefined. Although it has been applied in interhospital pretransfer, ( 11 - 13 ) its use at the time of transfer between sectors of the same hospital has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%